2021
DOI: 10.12657/folmal.029.009
|View full text |Cite
|
Sign up to set email alerts
|

The superfamilies Pupilloidea and Enoidea (Gastropoda, Eupulmonata) in Bhutan

Abstract: The species of two gastropod superfamilies, i.e. Pupilloidea and Enoidea, that have been recorded in Bhutan, are described and illustrated. Five families with ten species in total are dealt with. Three species are described as new to science, viz. Pupisoma (P.) paroense Gittenberger et Leda, n. sp., Pseudonapaeus occibhutanus Gittenberger, Gyeltshen et Sherub, n. sp., and Laevozebrinus parvus Gittenberger, Gyeltshen et Leda, n. sp. Distribution maps are presented for all the species. Some biogeographical consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although a few studies ( Páll-Gergely et al 2015b , 2021 ) have shown that some Southeast Asian terrestrial snail species are widely distributed over several hundreds of kilometres, this condition has not yet been observed amongst the smallest microsnails. Probably the only known example is Bensonella plicidens (Benson, 1849), which was claimed to have a disjunct distribution in the Himalaya and in East Asia, including Japan and eastern China (see Pilsbry 1918; Gittenberger et al 2021 ). However, recent study has shown that the Himalayan and East Asian species belong to two distinct species ( Páll-Gergely and White 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies ( Páll-Gergely et al 2015b , 2021 ) have shown that some Southeast Asian terrestrial snail species are widely distributed over several hundreds of kilometres, this condition has not yet been observed amongst the smallest microsnails. Probably the only known example is Bensonella plicidens (Benson, 1849), which was claimed to have a disjunct distribution in the Himalaya and in East Asia, including Japan and eastern China (see Pilsbry 1918; Gittenberger et al 2021 ). However, recent study has shown that the Himalayan and East Asian species belong to two distinct species ( Páll-Gergely and White 2023 ).…”
Section: Introductionmentioning
confidence: 99%